[Wanted Site for trash ; Logging in Laguna ; Color my world [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Discusses the residents complaint on the location of dumpsites by the government in Camarin, Caloocan City; illegal logging in Majayjay, Laguna; and the color fashion tip.